Predicting Mastectomy Skin Flap Necrosis in Immediate Breast Reconstruction - SAÇAK, BÜLENT; ÖNAL, MUSTAFA; UĞURLU, MUSTAFA ÜMİT; AKDENİZ DOĞAN, ZEYNEP DENİZ (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2021)
Background: As evidence emerged supporting the oncological safety of nipple-sparing mastectomy (NSM), immediate reconstruction following these procedures has also gained popularity. The aim of this study was to identify surgical and patient characteristics that may be associated with skin and/or NAC necrosis following NSM and immediate reconstruction. Patients and Methods: Medical records of patients who underwent NSM with immediate breast reconstruction from January 2013 to September 2020 were retrospectively reviewed. Patient and surgical characteristics were collected. The primary outcome measure was mastectomy skin flap necrosis (MSFN). Results: MSFN was observed in 68 out of 243 (28%) breasts. On univariate analysis, reconstruction method and body mass index (BMI) (odds ratio: 1.09, 95% confidence interval: 1.00-1.18, P = 0.04) were found to be significant risk factors. On multivariate analysis, neither BMI (P = 0.30) nor reconstruction methods (implants (P = 0.16) or tissue expander (P = 0.06) showed significant association with skin flap necrosis. However, BMI was found to be significantly higher in the autologous group (P < 0.0001). The best subset selection method also confirmed the reconstruction method as the single variable related to outcome. Conclusion: Even though our results showed autologous reconstruction to have a higher risk for necrotic complications, it should be kept in mind that this group of patients can be managed in the outpatient clinic with debridement, wound care, and - if necessary - skin grafting. However, full-thickness necrosis in an implant patient will require an implant exchange and possibly a local skin/muscle flap for coverage.
Keywords: Breast reconstruction; mastectomy skin flap necrosis; nipple-sparing mastectomy